Application of LOICZ DPSIR framework to South asia Basins and developing typology for coastal vulnerability in South Asia - Ganapuram, Sreedhar (2011)
Dissertação de Mestrado, Gestão da Água e da Costa, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2007